Organization of A3-coupling compounds by magnetic nanocomposite bimetallic in green conditions - Mansour Binandeh; Mohammad Ali Nasseri; Ali Allahresani (PLoS ONE, 2025)
The current project reports two chemical reactions of A3 coupling and creation of three reactans simultaneously and in domino form by bimetallic magnetic nanocatalyst (cobalt/manganese). This bimetallic nanocatalyst was heterogeneously synthesized by a simple chemical co-precipitation method and identified and analyzed by FE-SEM, TEM, VSM, ICP, BET, FT-IR, EDX, etc. analyses. The experimental results showed that the structure of the nanocatalyst is very regular and flexible, and its surface has spaces in nanometer sizes to carry out these chemical reactions. The efficiency and power of the nanocatalyst is very high and it has a special feature for easy separation from the reaction by an external field. The performed triple coupling reactions include the formation of the imide product, the propargylic product. The derivatives of this product each have a high percentage of 76% and selectivity of 98%. These products are widely used in new precursors for making antioxidant and antimicrobial drugs in medical and chemical industries.